2023
DOI: 10.3390/microorganisms11040960
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Molecular Culture in Early Onset Neonatal Sepsis Diagnosis: A Proof of Principle Study

Abstract: Delay in the time-to-positivity of a peripheral blood culture (PBC), the gold standard for early onset neonatal sepsis (EOS) diagnosis, has resulted in excessive use of antibiotics. In this study, we evaluate the potential of the rapid Molecular Culture (MC) assay for quick EOS diagnosis. In the first part of this study, known positive and spiked blood samples were used to assess the performance of MC. In the in vivo clinical study, the second part of this study, all infants receiving antibiotics for suspicion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The multiplex PCR test which was used in our study (LightCycler ® SeptiFast MGRADE system, Roche Diagnostics, Penzberg, Germany) is no longer commercially available. Even as metagenomic NGS methods emerge that do not necessitate specific primer design, allowing for the detection of a broad spectrum of bacterial, fungal, and viral pathogens in one assay [27][28][29] and have the potential to detect antimicrobial resistance genes, we believe our study's results would remain largely consistent. Even though the multiplex PCR we employed already encompassed the most common pathogens associated with EONS, the diagnostic yield was not enhanced for culture-negative patients diagnosed with EONS based on clinical, laboratory, and anamnestic indicators (EONS group two).…”
Section: Discussionmentioning
confidence: 63%
“…The multiplex PCR test which was used in our study (LightCycler ® SeptiFast MGRADE system, Roche Diagnostics, Penzberg, Germany) is no longer commercially available. Even as metagenomic NGS methods emerge that do not necessitate specific primer design, allowing for the detection of a broad spectrum of bacterial, fungal, and viral pathogens in one assay [27][28][29] and have the potential to detect antimicrobial resistance genes, we believe our study's results would remain largely consistent. Even though the multiplex PCR we employed already encompassed the most common pathogens associated with EONS, the diagnostic yield was not enhanced for culture-negative patients diagnosed with EONS based on clinical, laboratory, and anamnestic indicators (EONS group two).…”
Section: Discussionmentioning
confidence: 63%
“…The advantages of molecular culture included its capability to detect bacteria, even with a low bacterial load, with results available within 4 h. Moreover, molecular culture successfully identified Enterococcus faecalis in a case of clinical EOS with negative blood culture, showcasing its effectiveness in detecting microorganism challenges to identify using conventional techniques. The authors suggested that molecular culture could potentially replace traditional blood culture in EOS diagnostics, providing guidance to clinicians on the appropriate timing to discontinue antibiotic therapy shortly after birth [44]. However, it is crucial to acknowledge several limitations of this study.…”
Section: Molecular Culturementioning
confidence: 99%
“…In a more recent study, involving a notably smaller cohort of 38 neonates, an unrestricted PCR-based technique was assessed. This method detects and identifies bacterial DNA through the 16S-23S rRNA gene interspace regions, termed as rapid molecular culture [44]. Interestingly, blood culture yielded negative results for all participants, while molecular culture indicated positivity in three cases (7.5%).…”
Section: Molecular Culturementioning
confidence: 99%
“… 35 , 46 These techniques may be able to provide a more rapid diagnosis and require less labour time from laboratory staff. 43 , 47 However, the accuracy of these tests is not yet sufficient to entirely replace traditional culture methods, 46 , 48 and are at present too costly to be used in a resource-limited setting. 43 , 49 Many commercially available kits have too high a sensitivity leading to false positives where a contaminant has been detected, and do not yet provide any information on antimicrobial susceptibility.…”
Section: Diagnosticsmentioning
confidence: 99%